(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The research aims to determine the relationship between the application of e-governance and simplifying work procedures in healthcare departments, specifically in Iraqi Health Insurance Commission (HIC). The research is based on "How can e-governance assist in simplifying work procedures and raising their efficiency in health care departments, specifically in the HIA", thus raising the level of performance and effectiveness in the technology field, in a way that shortens and simplifies unnecessary procedures in the workflow in HIC, the importance of this research lies in highlighting and focusing on the increasing interest in e-governance practices through automating HIC’s activities. The study addressed two variables: the first is the independent variable of electronic governance, and the second is the dependent variable of simplifying work procedures. The research sample was selected from 130 HIC employees. To test the hypotheses, this hypothesis was tested through a descriptive-analytical method, and a questionnaire was used as a tool for data collection, in addition to direct observation of the authority’s actual reality. The research assumed the existence of a significant statistical correlation and impact relationship between e-governance and the simplification of work procedures. The research aims to reach a set of conclusions and recommendations that can benefit researchers in the studied authority.